The Role of Principal and Secondary Diagnoses of Hospitalized Eye Trauma: A Nationwide Cohort in Taiwan, 1996-2010 - Lee, Jiahn-Shing (PLoS One, 2015)
PURPOSE: To estimate the rate of hospitalized eye trauma in Taiwan and investigate the role between principal and secondary diagnoses of such trauma. METHODS: Nationwide fixed cohort study of 1,000,000 beneficiaries from the Taiwan Longitudinal Health Database was used and 4819 patients who were hospitalized for eye trauma during 1996-2010 were analyzed. RESULTS: During 1996-2010, the incidence rates of hospitalized eye trauma (per 100 000 person-years) were 35.0 (95% confidence interval (CI), 34.0 to 36.0) for total diagnosis, 9.8 (95% CI, 9.3 to 10.3) for a principal diagnosis, and 25.3 (95% CI, 24.4 to 26.1) for a secondary diagnosis. The sex risk ratio was 3.1 for a principal diagnosis and 2.1 for a secondary diagnosis. The main causes of eye trauma were traffic accident, work accident, assault (among males <60 years of age), and falls (among elderly men and women). The proportion admitted to an ophthalmic department among those with a principal diagnosis of eye trauma (64.8%) was significantly higher than among those with a secondary diagnosis (2.3%) (p<.0001). Patients with a principal diagnosis of eye trauma had shorter hospital stays (7.1±10.2 days) and lower fatality (0.07%) than those with a secondary diagnosis of eye trauma (10.0±31.6 days and 0.3%, respectively). CONCLUSION: Data only from ophthalmic admissions tends to underestimate the true incidence rate of hospitalized eye trauma. Patients with a principal diagnosis of eye trauma had less severe injuries than did those with a secondary diagnosis.